Scaling up local energy infrastructure; An agent-based model of the emergence of district heating networks. (January 2017) - Busch, Jonathan; Roelich, Katy; Bale, Catherine S.E.; Knoeri, Christof
Abstract: The potential contribution of local energy infrastructure – such as heat networks – to the transition to a low carbon economy is increasingly recognised in international, national and municipal policy. Creating the policy environment to foster the scaling up of local energy infrastructure is, however, still challenging; despite national policy action and local authority interest the growth of heat networks in UK cities remains slow. Techno-economic energy system models commonly used to inform policy are not designed to address institutional and governance barriers. We present an agent-based model of heat network development in UK cities in which policy interventions aimed at the institutional and governance barriers faced by diverse actors can be explored. Three types of project instigators are included – municipal, commercial and community – which have distinct decision heuristics and capabilities and follow a multi-stage development process. Scenarios of policy interventions developed in a companion modelling approach indicate that the effect of interventions differs between actors depending on their capabilities. Successful interventions account for the specific motivations and capabilities of different actors, provide a portfolio of support along the development process and recognise the important strategic role of local authorities in supporting low carbon energy infrastructure. Highlights: Energy policy should account for diverse actor motivations and capabilities. Project development is a multi-stage process, not a one-off event. Participatory agent-based modelling can inform policy that accounts for complexity. Policy should take a portfolio approach to providing support. Local authorities have an important strategic role in local infrastructure.